Intraventricular Hemorrhage Extension is a Strong Predictor of Mortality in Hemorrhagic Stroke - Al Mamun, Sk Abdullah; Rahman Sheikh, Md Sayedur; Rahman, Md Zahidur; Wadud, Md Abdul; Iffat, Musfiqa (Medicine Today, 2023)
Introduction: Spontaneous intracerebral hemorrhage (sICH) accounts for 10–15% of all strokes and is characterized by a 30–50% 3-month mortality rate. Intraventricular hemorrhage (IVH) extension can be seen in up to 54% of spontaneous intracerebral hemorrhage and is an independent predictor of worse outcome and neurological deterioration. Objective: To predict outcome and prognosis in spontaneous intracerebral hemorrhage patient in relation with intraventricular hemorrhage extension. Materials and Methods: Hospital based prospective study carried out in two hundred hemorrhagic stroke patients. The severity of intraventricular hemorrhage extension was calculated using the Graeb scale and volume of hemorrhage was measured by ABC/2 formula using CT scan. Results: Mean age of patients of hemorrhagic stroke was 61.64 ± 12.76 years. 66% of patients were male. Mortality rate of hemorrhagic stroke after the age of 60 years was 47.92% in 1st month. 79.80% of patients were died with GCS score less than 8. In our study 96.08% of patient died with >50 ml Hemorrhage group, on the other hand mortality rate was 48% in 30-50ml hemorrhage group and 11.12% in <30ml hemorrhage group. Mortality rate was 61.17% in hemorrhagic stroke with ventricular extension group on the other hand mortality was 21.65% in hemorrhagic stroke without ventricular extension. Those patients with GRAEB score >5 their mortality rate was 75.00% on the other hand mortality was 49.10% in GRAEB score 1-4. Conclusion: Intraventricular hemorrhage extension increased mortality in spontaneous intracerebral hemorrhage. Increased IVH extension severity, defined by a GRAEB score _5, is an independent predictor of poor outcome of Spontaneous intracerebral hemorrhage alone with age, GCS and hemorrhage volume. Medicine Today 2023 Vol.35(1): 34-39